Insulin self-administration technique with disposable syringe among patients with diabetes mellitus followed by the family health strategy Técnica de auto aplicación de insulina con jeringas desechables entre usuarios con diabetes mellitus acompañados por la estrategia salud de la familia Técnica de autoaplicação de insulina com seringas descartáveis entre os usuários com diabetes mellitus, acompanhados pela estratégia saúde da família - Thaís Santos Guerra Stacciarini; Ana Emilia Pace; Vanderlei José Haas (Universidade de São Paulo, 2009)
This cross-sectional study aimed to describe the most common correct and incorrect self-administration techniques for insulin using disposable syringes by patients cared for by the Family Health Strategy (FHS), relate the findings to sociodemographic variables and also identify the professional responsible for teaching this technique. A total of 169 patients were selected by simple random sampling in 37 FHS units in a city in the state of Minas Gerais, Brazil from August to October 2006. The results identified errors in all the steps recommended by the American Diabetes Association and Brazilian Diabetes Association for the safe administration of insulin, from hand washing to compression on the injection site. The FHS favors the development of interventions focused on the needs of the clientele registered at the unit, stimulating self-care. Results from this study can contribute to the planning of these interventions. Se trata de un estudio seccional que tuvo como objetivó describir los errores y los aciertos más comunes de la técnica de auto aplicación de insulina, con jeringas desechables, por los usuarios, acompañados por la Estrategia Salud de la Familia (ESF), así como relacionar lo encontrado a las variables sociodemográficas e identificar al profesional responsable por las orientaciones. Participaron 169 usuarios, seleccionados por medio de un muestreo aleatorio simple, en 37 unidades de la ESF, de un municipio del Estado de Minas Gerais, entre agosto y octubre de 2006. Los resultados identificaron errores en todos los pasos recomendados por la Asociación Americana de Diabetes y la Sociedad Brasileña de Diabetes para la aplicación segura de la insulina, desde el lavado de las manos hasta la compresión del local de aplicación. La ESF favorece el desarrollo de intervenciones con foco en las necesidades de la clientela adscrita, estimulándola para el auto cuidado, y los resultados del presente estudio podrán contribuir para la planificación de esas intervenciones. Estudo seccional que objetivou descrever os erros e os acertos mais comuns da técnica de autoaplicação de insulina, com seringas descartáveis, pelos usuários, acompanhados pela Estratégia Saúde da Família (ESF), assim como relacionar esses achados às variáveis sociodemográficas e identificar o profissional responsável pelas orientações. Participaram 169 usuários selecionados por meio de amostragem aleatória simples, em 37 unidades da ESF, de um município do Estado de Minas Gerais, entre agosto e outubro de 2006. Os resultados identificaram erros em todos os passos recomendados pela Associação Americana de Diabetes e Sociedade Brasileira de Diabetes para a aplicação segura da insulina, desde a lavagem das mãos até a compressão do local de aplicação. A ESF favorece o desenvolvimento de intervenções centradas nas necessidades da clientela adscrita, estimulando-a para o autocuidado, e os resultados do presente estudo poderão contribuir para o planejamento dessas intervenções.